PROMOSI CAREGIVER KELUARGA PADA MANAJEMEN HIPERGLIKEMI - Ni Ketut Sujati; M. Agung Akbar; Lisdahayati Lisdahayati; Citra Amelia Yulianti (NHM PRESS, 2022)
Around 75% of people with diabetes don’t know that they were diabetes mellitus. Efforts to overcome the problem of blood sugar levels are through education through the support of family caregivers. Objective: to describe the management of hyperglycemia in clients with unstable blood glukosa levels through promoting the role of family caregivers. This research is a case study design, carried in 2022. Two diabetics aged 47–71 years who experience unstable blood glucose levels, and a caregiver from the client appointed based on the results of deliberation. Subjects were given education on hyperglycemia management together at their home. Evaluation of the caregiver's learning ability and blood glucose stability was carried out in 3 visits. Results and Discussion: Nursing diagnosis readiness to increase caregiver knowledge is intervened with hyperglycemia management education. Caregivers are involved in the intervention of the client's blood glucose instability. In three visits, there were fluctuations in the results of a 2-hour blood glucose test, pp 456-160 mg/dl. Caregivers play an important role in the management of hyperglycemia in Diabetes Mellitus clients. Conclusion: Management of hyperglycemia requires the promotion of family caregivers so that there are key people who control the stability of their blood sugar. Suggestion: It is necessary to conduct a more in-depth study of learning to become a family caregiver with more complex and more complex methods and subjects.